2016
DOI: 10.1038/ncomms11260
|View full text |Cite
|
Sign up to set email alerts
|

Chemical ordering suppresses large-scale electronic phase separation in doped manganites

Abstract: For strongly correlated oxides, it has been a long-standing issue regarding the role of the chemical ordering of the dopants on the physical properties. Here, using unit cell by unit cell superlattice growth technique, we determine the role of chemical ordering of the Pr dopant in a colossal magnetoresistant (La1−yPry)1−xCaxMnO3 (LPCMO) system, which has been well known for its large length-scale electronic phase separation phenomena. Our experimental results show that the chemical ordering of Pr leads to mark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
39
2
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(43 citation statements)
references
References 52 publications
1
39
2
1
Order By: Relevance
“…Another important difference is that phase separation in manganites is associated with substantial intrinsic disorder due to cation mixing, and a recent study has demonstrated that chemical ordering of cations in (La 1− y Pr y ) 1−x Ca x MnO 3 suppresses long range phase separation 18 . CaFe 3 O 5 is in principle a stoichiometric material although small strain variations due to the 4% substitution of Fe for Ca observed in our polycrystalline sample may tip the local balance between the energies of the two ground states leading to phase coexistence.…”
Section: Resultsmentioning
confidence: 99%
“…Another important difference is that phase separation in manganites is associated with substantial intrinsic disorder due to cation mixing, and a recent study has demonstrated that chemical ordering of cations in (La 1− y Pr y ) 1−x Ca x MnO 3 suppresses long range phase separation 18 . CaFe 3 O 5 is in principle a stoichiometric material although small strain variations due to the 4% substitution of Fe for Ca observed in our polycrystalline sample may tip the local balance between the energies of the two ground states leading to phase coexistence.…”
Section: Resultsmentioning
confidence: 99%
“…In a broader sense, the term electronic phase separation is used whenever two or more phases with differing electronic or magnetic properties coexist on microscopic length scales, including cases where the electronic phase separation is driven by inhomogeneities of the chemical composition or structural disorder [45,46].…”
Section: Control Of Separate Electronic Phasesmentioning
confidence: 99%
“…For instance, the random distribution of dopants produces nanoscale electronic inhomogeneity in some of the high T c cuprates [3][4][5][6] , chemical ordering of Pr suppresses large-scale electronic phase separation in maganites 7 or charge ordering in CoO 2 layers intertwines with ordering of the mobile Na + ions in Na x CoO 2 .…”
Section: Introductionmentioning
confidence: 99%